Redirecting T cells to eradicate B-cell acute lymphoblastic leukemia: bispecific T-cell engagers and chimeric antigen receptors - Aldoss, Ibrahim; Nagorsen, Dirk (Leukemia, 2017)
Recent advances in antibody technology to harness T cells for cancer immunotherapy, particularly in the difficult-to-treat setting of relapsed/refractory acute lymphoblastic leukemia (r/r ALL), have led to innovative methods for directing cytotoxic T cells to specific surface antigens on cancer cells. One approach involves administration of soluble bispecific (or dual-affinity) antibody-based constructs that temporarily bridge T cells and cancer cells. Another approach infuses ex vivo-engineered T cells that express a surface plasma membrane-inserted antibody construct called a chimeric antigen receptor (CAR). Both bispecific antibodies and CARs circumvent natural target cell recognition by creating a physical connection between cytotoxic T cells and target cancer cells to activate a cytolysis signaling pathway; this connection allows essentially all cytotoxic T cells in a patient to be engaged because typical tumor cell resistance mechanisms (such as T-cell receptor specificity, antigen processing and presentation, and major histocompatibility complex context) are bypassed. Both the bispecific T-cell engager (BiTE) antibody construct blinatumomab and CD19-CARs are immunotherapies that have yielded encouraging remission rates in CD19-positive r/r ALL, suggesting that they might serve as definitive treatments or bridging therapies to allogeneic hematopoietic cell transplantation. With the introduction of these immunotherapies, new challenges arise related to unique toxicities and distinctive pathways of resistance. An increasing body of knowledge is being accumulated on how to predict, prevent, and manage such toxicities, which will help to better stratify patient risk and tailor treatments to minimize severe adverse events. A deeper understanding of the precise mechanisms of action and immune resistance, interaction with other novel agents in potential combinations, and optimization in the manufacturing process will help to advance immunotherapy outcomes in the r/r ALL setting.
Published: 28 December 2016
Gesehen am 13.09.2018